Biodegradation of polymeric contact lenses: A comprehensive review of biological activity - Lina M. Shaker; Atheer Fadhil Mahmood; Zainab Rzaij Mohammad; Firas F. Hussain; Ahmed Al-Amiery; Suha A. Mohammed; Mohammed A. Fayad (Results in Surfaces and Interfaces)
Polymeric contact lenses are widely used for vision correction but contribute to significant environmental challenges due to their non-biodegradable nature and improper disposal, which exacerbates the growing problem of plastic pollution. Millions of discarded contact lenses enter landfills and water systems annually, where they break down into microplastics, posing threats to aquatic ecosystems and human health. This review explores the biological processes involved in the degradation of these lenses, with a focus on the roles of microorganisms, enzymes, and environmental factors such as temperature, pH, and humidity. Understanding how these factors influence the breakdown of polymer chains offers valuable insights into developing sustainable disposal methods and environmentally friendly materials. By comprehensively examining the enzymatic mechanisms of contact lens degradation, this review aims to propose green technologies for polymer waste management and highlights the urgent need for multidisciplinary efforts to mitigate the environmental impact of polymeric lenses, thereby advancing the global agenda for environmental sustainability.